Suppression of hepatic ChREBP⍺-CYP2C50 axis-driven fatty acid oxidation sensitizes mice to diet-induced MASLD/MASH - Deqiang Zhang; Yuee Zhao; Gary Zhang; Daniel Lank; Sarah Cooke; Sujuan Wang; Alli Nuotio-Antar; Xin Tong; Lei Yin (Elsevier, 2024)
Objectives: Compromised hepatic fatty acid oxidation (FAO) has been observed in human MASH patients and animal models of MASLD/MASH. It remains poorly understood how and when the hepatic FAO pathway is suppressed during the progression of MASLD towards MASH. Hepatic ChREBP⍺ is a classical lipogenic transcription factor that responds to the intake of dietary sugars. Methods: We examined its role in regulating hepatocyte fatty acid oxidation (FAO) and the impact of hepatic Chrebpa deficiency on sensitivity to diet-induced MASLD/MASH in mice. Results: We discovered that hepatocyte ChREBP⍺ is both necessary and sufficient to maintain FAO in a cell-autonomous manner independently of its DNA-binding activity. Supplementation of synthetic PPAR⍺/δ agonist is sufficient to restore FAO in Chrebp−/− primary mouse hepatocytes. Hepatic ChREBP⍺ was decreased in mouse models of diet-induced MAFSLD/MASH and in patients with MASH. Hepatocyte-specific Chrebp⍺ knockout impaired FAO, aggravated liver steatosis and inflammation, leading to early-onset fibrosis in response to diet-induced MASH. Conversely, liver overexpression of ChREBP⍺-WT or its non-lipogenic mutant enhanced FAO, reduced lipid deposition, and alleviated liver injury, inflammation, and fibrosis. RNA-seq analysis identified the CYP450 epoxygenase (CYP2C50) pathway of arachidonic acid metabolism as a novel target of ChREBP⍺. Over-expression of CYP2C50 partially restores hepatic FAO in primary hepatocytes with Chrebp⍺ deficiency and attenuates preexisting MASH in the livers of hepatocyte-specific Chrebp⍺-deleted mice. Conclusions: Our findings support the protective role of hepatocyte ChREBPa against diet-induced MASLD/MASH in mouse models in part via promoting CYP2C50-driven FAO.